2009
DOI: 10.1002/uog.6321
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric (3D) imaging reduces inter‐ and intraobserver variation of fetal biometry measurements

Abstract: Objective To compare the inter-and intraobserver variation of fetal biometric measurements utilizing twodimensional (2D) and three-dimensional (3D) ultrasound imaging. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 10 publications
4
36
1
Order By: Relevance
“…Similar findings have been reported before, demonstrating the potential use of 3D ultrasound in training of sonographers, in assessing their skills, and in improving basic obstetric biometric measurement [12][13][14]. Most modern obstetric ultrasound scanners are now equipped with 3D capability.…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings have been reported before, demonstrating the potential use of 3D ultrasound in training of sonographers, in assessing their skills, and in improving basic obstetric biometric measurement [12][13][14]. Most modern obstetric ultrasound scanners are now equipped with 3D capability.…”
Section: Discussionsupporting
confidence: 81%
“…Three dimensional US (3D-US) offers volumetric assessment of the placenta, which provides increased accuracy of placental growth compared to standard two-dimensional measures of length or thickness, while also minimizing errors of measurement (44). Early studies of placental volume using 3D-US in the first trimester have been shown to predict preeclampsia and fetal growth restriction.…”
Section: The Role Of Ultrasound In Placental Evaluationmentioning
confidence: 99%
“…These quantitative MRI studies are providing important insights into the rate and progression of placental growth in the healthy and high-risk pregnancy in utero. As discussed earlier, 3D volumetric imaging has demonstrated more accurate measurement of fetal biometry (44) and shown that biometric measures such as placental length alone, are insufficient clinical markers of fetal growth (57, 58). Moreover, 3D-MR imaging of the placenta provides more reliable measures of growth compared to 3D US (59, 60).…”
Section: Role Of Magnetic Resonance Imaging In Assessing Placental Hementioning
confidence: 99%
“…The advantage of such data is in visualization of planes in which 2-D acquisition is not possible, surface rendering of anatomies, and postexam data processing and review [2]. The 3-D acquisition decreases the examination time [4], [5] and reduces inter-and intra-observer variations of biometric measurements [3], especially for less experienced sonographers. Similar to 2-D exams, the major bottleneck remains the navigation to the standardized planes [6], in which measurements are performed.…”
Section: Automatic Detection and Measurement Of Structures In Fetal Hmentioning
confidence: 99%
“…The idea of importance sampling is to introduce a proposal distribution which includes the support of . In order for the samples to be proper [41], the weights are defined as (3) Since the current states do not depend on observations from other objects then (4) Note, that was left out of the first term since the states in the sequence do not depend on it. The states are computed as (5) Substituting (4) and (5) into (3), we have (6) (7) (8) In this paper, we adopt the transition prior as the proposal distribution.…”
Section: Sequential Sampling For Multi-object Detectionmentioning
confidence: 99%